Meteoric CaO and carbon smoke particles collected in the upper stratosphere from an unanticipated source - DELLA CORTE, VINCENZO; ROTUNDI, Alessandra; FERRARI, MARCO; PALUMBO, Pasquale; Rietmeijer, F. J. M. (Tellus B: Chemical and Physical Meteorology, 2013)
Nanometre CaO and pure carbon smoke particles were collected at 38-km altitude in the upper stratosphere in the Arctic during June 2008 using DUSTER (Dust in the Upper Stratosphere Tracking Experiment and Retrieval). This balloon-borne instrument was designed for non-destructive collection of solid particles between 200 nm to 40 mm. We report here on micrometre CaCO3 (calcite) grains with evidence of thermal erosion and smoke particles that formed after melting and vaporisation and complete dissociation of some of the CaCO3 grains at temperatures of approximately 3500 K. These conditions and processes suggest that the environment of this dust was a dense dust cloud that had formed after disintegration of a carbonaceous meteoroid during deceleration in the atmosphere. The balloon-borne collector must have coincidentally travelled through the dust cloud of a recent bolide event that had penetrated between 38.5 and 37 km altitude. This work identified a previously unknown meteoric smoke forming process in addition to meteoric smoke particles due to photolysis-driven oxidation of mesospheric metals from meteor ablation that had settled into the upper stratosphere.